Dlaczego zarządzający przedsiębiorstwami i audytorzy ukrywają i fałszują informacje - okazje i pokusy - Misińska, Danuta (Why to Managers of Enterprises and Auditors Coyer up and Falsify Information - Occasions and Opportunities, 2005)
In American and European companies we can observe falsifying of report information. Manipulation and falsifying are connected with violation of accounting principles by those managers and auditors who prefer summary, particular benefit. Prevention of there manipulations is possible through credible holder supervision.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2005; nr 1073, s. 181-191